Logistical, cultural, and structural barriers to immediate neonatal care and neonatal resuscitation in Bihar, India - Brennan Vail; Melissa C. Morgan; Jessica Dyer; Amelia Christmas; Susanna R. Cohen; Megha Joshi; Aboli Gore; Tanmay Mahapatra; Dilys M. Walker (BMC, 2018)
Abstract Background In India, the neonatal mortality rate is nearly double the Sustainable Development Goal target with more than half of neonatal deaths occurring in only four states, one of which is Bihar. Evaluations of immediate neonatal care and neonatal resuscitation skills in Bihar have demonstrated a need for significant improvement. However, barriers to evidence based practices in clinical care remain incompletely characterized. Methods To better understand such barriers, semi-structured interviews were conducted with 18 nurses who participated as mentors in the AMANAT maternal and child health quality improvement project, implemented by CARE India and the Government of Bihar. Nurse-mentors worked in primary health centers throughout Bihar facilitating PRONTO International emergency obstetric and neonatal simulations for nurse-mentees in addition to providing direct supervision of clinical care. Interviews focused on mentors' perceptions of barriers to evidence based practices in immediate neonatal care and neonatal resuscitation faced by mentees employed at Bihar's rural primary health centers. Data was analyzed using the thematic content approach. Results Mentors identified numerous interacting logistical, cultural, and structural barriers to care. Logistical barriers included poor facility layout, supply issues, human resource shortages, and problems with the local referral system. Cultural barriers included norms such as male infant preference, traditional clinical practices, hierarchy in the labor room, and interpersonal relations amongst staff as well as with patients' relatives. Poverty was described as an overarching structural barrier. Conclusion Interacting logistical, cultural and structural barriers affect all aspects of immediate neonatal care and resuscitation in Bihar. These barriers must be addressed in any intervention focused on improving providers' clinical skills. Strategic local partnerships are vital to addressing such barriers and to contextualizing skills-based trainings developed in Western contexts to achieve the desired impact of reducing neonatal mortality.